Experimental set-up and numerical optimization of a heavy-duty single-point SI engine fueled with ethanol for a generator set - D. Perrone; B. Falbo; T. Castiglione (Fuel, 2026)

Interpreting Fentanyl and Norfentanyl Concentrations among Patients Seen in the Emergency Department after a Nonfatal Opioid Overdose: A Multicenter Study - Jessica T. Kent; Rachel Culbreth; Jacob A. Lebin; Keith Burkhart; Robert G. Hendrickson; Zachary D. W. Dezman; Kim Aldy; Jeffrey Brent; Alyssa Falise; Sharan Campleman; Barry K. Logan; Michael Levine; et al. (Journal of Medical Toxicology, 2026)

Progress status of the NUSES Space Mission - M. Abdullahi; R. Aloisio; S. Ashurov; U. Atalay; F.C.T. Barbato; R. Battiston; M.E. Bertaina; E. Bissaldi; D. Boncioli; L. Burmistrov; I. Cagnoli; E. Casilli; et al. (Advances in Space Research, 2026)

Deep multiparameter analysis of the precursory lithospheric, atmospheric and ionospheric anomalies before and during the 28 March 2025 Mw7.7 Myanmar-Burma earthquake - Angelo De Santis; Xuemin Zhang; Saioa A. Campuzano; Pan Xiong; Gianfranco Cianchini; Jing Liu; Serena D'Arcangelo; Na Yang; Mariagrazia De Caro; Xinyan Ouyang; Martina Orlando; Maoning Feng; et al. (Tectonophysics, 2026)

The Lithosphere-Atmosphere-Ionosphere coupling (LAIC) processes around the 2024 Wushi (China) Mw7.1 earthquake - Xuemin Zhang; Angelo De Santis; Pan Xiong; Gianfranco Cianchini; Aisa Yisimayili; Saioa A. Campuzano; Na Yang; Serena D’Arcangelo; Jing Liu; Mariagrazia De Caro; Xinyan Li; Cristiano Fidani; et al. (Journal of Asian Earth Sciences, 2026)

Design and performance of the Low-Energy Module for the Ziré instrument on the NUSES mission: A compact spectrometer for low-energy particles in space high-radiation environments - Muhammd Abdullahi; Roberto Aloisio; Francesco Arneodo; Sindorjon Ashurov; Uygar Atalay; Felicia C.T. Barbato; Roberto Battiston; Mario Bertaina; Elisabetta Bissaldi; Denise Boncioli; Leonid Burmistrov; Franck Cadoux; et al. (Advances in Space Research, 2026)

A CNN Autoencoder for Learning Latent Disc Geometry from Segmented Lumbar Spine MRI - Mattia Perrone; D’Mar M. Moore; Daisuke Ukeba; John T. Martin (Annals of Biomedical Engineering, 2025)

Harnessing H2O2-induced susceptibility in Galleria mellonella larvae: A robust model for exploring oxidative stress and biomarkers - L.M.M. Mattos; R.N. Silva; L.G. Santos; L. Giovanini; V.S. Cruz; N.M.B. Barreto; D. Perrone; A.L.S. Santos; M.D. Pereira (Environmental Toxicology and Pharmacology, 2025)

The role of soybean meal extracts proteins in the inhibition of mild steel acid corrosion - Klícia Carla de Santana de Lima; Victor Magno Paiva; Marcos Gustavo Araujo Schwarz; Nathália Martins Bomfim Barreto; Daniel Perrone; Eliane D'Elia (Sustainable Chemistry and Pharmacy, 2023)

MiR-126 and miR-146a as Melatonin-Responsive Biomarkers for Neonatal Brain Ischemia - Maria Cristina Albertini; Tania Vanzolini; Serafina Perrone; Michael D. Weiss; Giuseppe Buonocore; Valentina Dell’Orto; Walter Balduini; Silvia Carloni (Journal of Molecular Neuroscience, 2023)
Despite advances in obstetric and neonatal care, challenges remain in early identification of neonates with encephalopathy due to hypoxia-ischemia who are undergoing therapeutic hypothermia. Therefore, there is a deep search for biomarkers that can identify brain injury. The aims of this study were to investigate the serum and brain expressions of two potential biomarkers, miR-126/miR-146a, in a preclinical model of hypoxia-ischemia (HI)–induced brain injury, and to explore their modulation during melatonin treatment. Seven-day-old rats were subjected to permanent ligation of the right carotid artery followed by 2.5 h hypoxia (HI). Melatonin (15 mg/kg) was administered 5 min after HI. Serum and brain samples were collected 1, 6 and 24 h after HI. Results show that HI caused a significant increase in the circulating levels of both miR-126 and miR-146a during the early phase of ischemic brain damage development (i.e. 1 h), with a parallel and opposite pattern in the ischemic cerebral cortex. These effects are not observed 24 h later. Treatment with melatonin restored the HI-induced effects on miR-126/miR-146a expressions, both in the cerebral cortex and in serum. We conclude that miR-126/miR-146a are promising biomarkers of HI injury and demonstrate an associated change in concentration following melatonin treatment.

Seismic risk assessment of masonry-infilled RC building portfolios: impact of variability in the infill properties - G. Mucedero; D. Perrone; R. Monteiro (Bulletin of Earthquake Engineering, 2023)

A Brief Educational Intervention to Increase ED Initiation of Buprenorphine for Opioid Use Disorder (OUD) - Utsha G. Khatri; Kathleen Lee; Theodore Lin; Joseph L. D’Orazio; Mitesh S. Patel; Frances S. Shofer; Jeanmarie Perrone (Journal of Medical Toxicology, 2022)

Nonlinear static characterisation of masonry-infilled RC building portfolios accounting for variability of infill properties - G. Mucedero; D. Perrone; R. Monteiro (Bulletin of Earthquake Engineering, 2021)

Revised Accelerated Moment Release Under Test: Fourteen Worldwide Real Case Studies in 2014–2018 and Simulations - Gianfranco Cianchini; Angelo De Santis; Rita Di Giovambattista; C. Abbattista; L. Amoruso; S. A. Campuzano; M. Carbone; C. Cesaroni; Anna De Santis; D. Marchetti; L. Perrone; A. Piscini; et al. (Pure and Applied Geophysics, 2020)

Seismic performance of non-structural elements during the 2016 Central Italy earthquake - D. Perrone; P. M. Calvi; R. Nascimbene; E. C. Fischer; G. Magliulo (Bulletin of Earthquake Engineering, 2019)

Chemically and size-resolved particulate matter dry deposition on stone and surrogate surfaces inside and outside the low emission zone of Milan: application of a newly developed “Deposition Box” - Luca Ferrero; Marco Casati; Lara Nobili; Luca D’Angelo; Grazia Rovelli; Giorgia Sangiorgi; Cristiana Rizzi; Maria Grazia Perrone; Antonio Sansonetti; Claudia Conti; Ezio Bolzacchini; Elena Bernardi; et al. (Environmental Science and Pollution Research, 2018)

Multimodal Neuroimaging in Schizophrenia: Description and Dissemination - C. J. Aine; H. J. Bockholt; J. R. Bustillo; J. M. Cañive; A. Caprihan; C. Gasparovic; F. M. Hanlon; J. M. Houck; R. E. Jung; J. Lauriello; J. Liu; A. R. Mayer; et al. (Neuroinformatics, 2017)

Spatio-temporal monitoring by ground-based and air- and space-borne lidars of a moderate Saharan dust event affecting southern Europe in June 2013 in the framework of the ADRIMED/ChArMEx campaign - R. Barragan; M. Sicard; J. Totems; J. F. Léon; F. Dulac; M. Mallet; J. Pelon; L. Alados-Arboledas; A. Amodeo; P. Augustin; A. Boselli; J. A. Bravo-Aranda; et al. (Air Quality, Atmosphere & Health, 2017)

Contribution of EARLINET/ACTRIS to the summer 2013 Special Observing Period of the ChArMEx project: monitoring of a Saharan dust event over the western and central Mediterranean - M. Sicard; R. Barragan; C. Muñoz-Porcar; A. Comerón; M. Mallet; F. Dulac; J. Pelon; L. Alados Arboledas; A. Amodeo; A. Boselli; J. A. Bravo-Aranda; G. D’amico; et al. (International Journal of Remote Sensing, 2016)

Determination of aerosol deliquescence and crystallization relative humidity for energy saving in free-cooled data centers - L. Ferrero; L. D’Angelo; G. Rovelli; G. Sangiorgi; M. G. Perrone; M. Moscatelli; M. Casati; V. Rozzoni; E. Bolzacchini (International Journal of Environmental Science and Technology, 2015)

Epidemiological analysis on two decades of hospitalisations for meningitis in the United States - P. Pellegrino; C. Carnovale; V. Perrone; D. Salvati; M. Gentili; T. Brusadelli; S. Antoniazzi; M. Pozzi; S. Radice; E. Clementi (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Short-term effects of soil solarization in suppressing Calonectria microsclerotia - Alessandro Vitale; Ivana Castello; Alessandro D’Emilio; Rosalia Mazzarella; Giancarlo Perrone; Filomena Epifani; Giancarlo Polizzi (Plant and Soil, 2013)

Cystic fibrosis Δf508 mutation screening in Brazilian women with altered fertility - G. V. F. Brunoro; E. V. Wolfgramm; I. D. Louro; I. I. Degasperi; V. C. W. Busatto; A. M. S. Perrone; M. C. P. Batitucci (Molecular Biology Reports, 2011)

A Biomonitoring Study Assessing the Residual Biological Effects of Pollution Caused by the HAVEN Wreck on Marine Organisms in the Ligurian Sea (Italy) - A. Viarengo; F. Dondero; D. M. Pampanin; R. Fabbri; E. Poggi; M. Malizia; C. Bolognesi; E. Perrone; E. Gollo; G. P. Cossa (Archives of Environmental Contamination and Toxicology, 2007)

HPLC analyses of seed storage proteins reveal polymorphism in Italian common bean (Phaseolus vulgaris L.) ecotypes - Giuseppe Mennella; Vincenzo Onofaro Sanajà; Antonietta D'Alessandro; Marco Milone; Domenico Perrone (Euphytica, 2003)

Persistent Organochlorine Pollutants in Liver of Birds of Different Trophic Levels from Coastal Areas of Campania, Italy - B. Naso; D. Perrone; M. C. Ferrante; A. Zaccaroni; A. Lucisano (Archives of Environmental Contamination and Toxicology, 2003)